Pengaruh Kepuasan Kerja dan Loyalitas Karyawan terhadap Kinerja Karyawan Foods Manufacture - Nabilla Salsabil Sausan; Amrin Mulia Utama Nasution; Hesti Sabrina (Economics, Business and Management Science Journal, 2021)
This study aims to determine how the effect of job satisfaction and employee loyalty on the performance of employees of PT. Asia Sakti Wahid Foods Manufacture Medan. The research sample is employees at PT. Asia Sakti Wahid Foods Manufacture Medan. This type of research is associative research, where variables are measured on a Likert scale. Data collection method is done by interview and questionnaire. In this study the sample used was 65 respondents. Data processing using SPSS 22.0. With descriptive analysis and hypothesis testing multiple linear regression analysis. The results showed that there was a positive and significant effect on job satisfaction on the performance of employees of PT. Asia Sakti Wahid Foods Manufacture Medan. In the variable employee loyalty shows that there is a positive and significant effect on the performance of employees of PT. Asia Sakti Wahid Foods Manufacture Medan.